Registros de mayor altitud para mosquitos (Diptera: Culicidae) en Venezuela - Navarro, Juan-Carlos; Del Ventura, Fabiola; Zorrilla, Adriana; Liria, Jonathan (Revista de Biología Tropical, 2010)
Mosquitoes (Diptera: Culicidae) are holometabolous insects with aquatic immature stages, which use a broad variety of larval habitats, from ground water bodies to Phytothelmata (water deposits in plants) and artificial deposits. The availability of breeding sites often determines the upper limits of mosquito ranges. We built a database with 9 607 records with 432 localities, 19 genera and 254 species. The Andean mountains have 77% of the highest mosquito records including Aedes euris with record at 3 133 m, followed by three species of Anopheles -subgenera Kerteszia- with the upper limit of 2 680 m. Wyeomyia bicornis and Culex daumastocampa at 2 550 m were the highest records in the Central-Coastal cordillera, while the highest record in Pantepui was Wyeomyia zinzala at 2 252 m. The species associ-ated with phytothelmata (Bromeliaceae and Sarraceniaceae) represent 60% of the records. The upper limits of Culex quinquefasciatus and Anopheles (Kerteszia) species could represent the theoretical limit for transmission of filariasis or arboviruses, by Culex, and malaria by Anopheles (Kerteszia) in Venezuela. Similarly, a vector of Dengue, Aedes aegypti, has not been not recorded above 2 000 m.